Some aspects of consumer protection in consumer credit - Зеленова, Марина Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The article deals with the problematic issues that have arisen in our country during the global financial crisis and are related to the fact that a certain part of the population of Ukraine received consumer credits not in national currency but in foreign. As a result, the sharp depreciation of the national currency, a significant portion of borrowers found themselves in a difficult financial position. The causes of this situation are analyzed. In particular, the article focuses on the fact that though the state was barred from receiving consumer loans in foreign currency, however, this step was made with a considerable delay, when consumer credit in foreign currency received considerable spread in Ukraine. It was also found that the blame for the poor financial position in the market of financial services is not only on the state but also within financial institutions which contrary to the requirements of the current legislation have not been properly raising awareness among consumers of financial services, not properly explained to the citizens of all the risks that may arise in connection with the receipt of consumer loans in foreign currency. Analysis of judicial practice allows us to conclude that banks in the vast majority formally belonged to perform their duties when making consumer loans in foreign currency and are not provided or provided in fuzzy or not understandable form information on the risks facing consumers wishing to obtain consumer loans in foreign currency. The article also analyzes a separate legal position in litigation with the banks. The attention is focused on the fact that this legal position changes frequently, and sometimes remains unchanged despite the fact that they do not meet the requirements of current legislation. At the end of the article it is concluded that the protection of consumer rights in the field of lending in foreign currency affects not only the legal but also the financial and social factors that have no less and sometimes even more influence on the decision of this question.